2004
DOI: 10.1002/bem.20015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static magnetic field on growth and sporulation of some plant pathogenic fungi

Abstract: Growth and sporulation of phytopathogenic microscopic fungi were studied under a static magnetic field. The applied flux densities were 0.1, 0.5, and 1 mT. The magnetic field decreased the growth of colonies by 10% using this flux density region. At 0.1 mT flux density, the deviations are significant, P =.001, while in other cases the deviations generally are not significant. At the same time, the number of the developed conidia of Alternaria alternata and Curvularia inaequalis increased by 68-133%, but the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Saccharomyces cereVisiae from the slant cultures was aseptically transferred and precultured in 500-mL Erlenmeyer flasks with 300 mL of the medium containing the following components [ (5). The Erlenmeyer flasks were incubated at 30°C and 200 rpm for 12 h. Fermentor was inoculated with 10% v/v concentrated inoculum, and the fermentations were carried out using a medium similar to those used for inoculum preparation but without glucose and adding (NH4) 2 SO 4 [11.75] and sugar cane molasses diluted to attain approximately 160 g L -1 sugar concentration as substitute for glucose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharomyces cereVisiae from the slant cultures was aseptically transferred and precultured in 500-mL Erlenmeyer flasks with 300 mL of the medium containing the following components [ (5). The Erlenmeyer flasks were incubated at 30°C and 200 rpm for 12 h. Fermentor was inoculated with 10% v/v concentrated inoculum, and the fermentations were carried out using a medium similar to those used for inoculum preparation but without glucose and adding (NH4) 2 SO 4 [11.75] and sugar cane molasses diluted to attain approximately 160 g L -1 sugar concentration as substitute for glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Saccharomyces cereVisiae used for ethanol production was supplied by Bioengineering Laboratory of the Food Engineering School of The State University of Campinas, Brazil. The microorganism was maintained at 5°C on agar slants whose medium contained [amounts in g L -1 ]: glucose [10], yeast extract [5], malt extract [3], pectin [5], and agar [20].…”
Section: Methodsmentioning
confidence: 99%
“…This can be combined with tropism of living organisms, especially microbes such as viruses, bacteria and fungi . The tip growing systems (fungal hyphae and mycelia) have natural tendencies to respond to external stimuli such as light, nutrients, physical contact, gravity, and electric and magnetic fields . Several studies have proved that light is a reliable tropic factor and stimulant to control the growth, morphology, and biochemical changes in plants and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The tip growing systems (fungal hyphae and mycelia) have natural tendencies to respond to external stimuli such as light, [ 17 ] nutrients, [ 18 ] physical contact, [ 19 ] gravity, [ 20 ] and electric and magnetic fi elds. [ 21,22 ] Several studies have proved that light is a reliable tropic factor and stimulant to control the growth, morphology, and biochemical changes in plants and fungi. Specifi cally the fungi can respond to light sources over a wide range of spectrum from ultraviolet to far infrared through a selective wavelength absorption process due to the presence of chromoprotiens and various photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation and ozonation combined with low concentrations of hydrogen peroxide (Heikkinen et al., ), and combinations of manual cleaning, formalin and salt treatments (Torres and Fajardo, ). Nagy and Fischl () found that at a magnetic flux density of 100 μ T, growth of the phytopathogenic fungi Alternaria alternata , Curvularia inaequalis and Fusarium oxysporum decreased by some 10%. As indicated in our preliminary studies, magnetic fields having specific values can also be an effective mycosis prophylaxis (Mazurkiewicz‐Zapałowicz et al., ).…”
Section: Introductionmentioning
confidence: 99%